Comprehensive evaluation of adsorption and degradation of tetracycline and oxytetracycline by nanoscale zero-valent iron - Hanay, Ozge; Turk, Hande (Desalination Publ, 2015)
The interaction of tetracycline (TC) and oxytetracycline (OTC) with nanoscale zero-valent iron (nZVI) was examined with a batch experimental series in order to determine the removal efficiency and transformation products. Experimental variables, such as solution pH, nZVI dosage, contact time, initial TCs concentration, and reaction temperature, were systematically studied. Adsorption kinetics showed that equilibrium was reached within 2 h according to the pseudo-second-order model. The adsorption behavior was pH-dependent and favored at pH 6 regardless of TC type considered due to electrostatic attraction between nZVI and TCs. The adsorption capacity of TC was more than that of OTC. The results of LC-MS-MS showed that main transformation product was 4-epi-tetracycline for TC and insignificant for OTC. On the other hand, desorption studies exhibited that nZVI adsorbed not only parent compounds but also transformation products. The results showed that the removal mechanism of TC and OTC by using nZVI surface was mainly the adsorption relatively than the degradation process.
Keywords: Nanoscale zero-valent iron; Tetracycline; Transformation product; Oxytetracycline